ANALISIS PELAKSANAAN PEMBELAJARAN SOSIOLOGI MENGGUNAKAN MEDIA PEMBELAJARAN BAMBOOZLE DI KELAS XII IPS 2 SMAN 1 SUNGAI RAYA KEPULAUAN KABUPATEN BENGKAYANG - Zalianty, Anindya; Ramadhan, Iwan; Zatalini, Adhalia (Digulis: Jurnal Pengabdian Pada Masyarakat, 2025)
This research aims to analyze the implementation of sociology learning using Bamboozle as a learning medium in class XII IPS 2 at SMAN 1 Sungai Raya Kepulauan, Bengkayang Regency. This research employs a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. The respondents of this study are sociology teachers and students of class XII IPS 2 at SMAN 1 Sungai Raya Kepulauan, Bengkayang Regency. The results indicate that the planning of sociology learning implementation involves the preparation of lesson plans (RPP), followed by planning steps on the Bamboozle platform, such as creating an account, accessing the Bamboozle website, and adding questions and answers relevant to the subject matter. The implementation of sociology learning using Bamboozle is carried out by utilizing its features and following the steps outlined in the lesson plan. Student learning outcomes using Bamboozle in sociology lessons show an improvement in conceptual understanding and an increase in average scores, as well as heightened student enthusiasm. In conclusion, the implementation of sociology learning using Bamboozle in class XII IPS 2 at SMAN 1 Sungai Raya Kepulauan, Bengkayang Regency, positively contributes to both the learning process and student outcomes in sociology. The implications of this research include recommendations for further development in the application of innovative and effective learning technologies in the educational context